Development as freedom in Brazil - Dalto, Karla Karoline Soares; Pires, Mônica Moura; Aguiar, Paulo César Bahia (Sociedade & Natureza, 2021)
The search for socio-economic development has been one of the main objectives to guide government policies in different countries. The deepening of the environmental crisis and the demand for well-being have led governments and society to discuss new models of development and instruments capable of measuring them. The present work is part of this theme by structuring an index of development backed by the studies of Amartya Sen, whose theory is based on the expansion of individual freedoms and the extinction of deprivations that restrict their opportunities. The main objective of this article is to analyze the socioeconomic reality of Brazilian federative units and regions by means of a Development as Freedom Index (DFI; Índice de Desenvolvimento como Liberdade - IDL) and sub-indices of Instrumental Freedoms advocated by Amartya Sen. To that end, the theoretical assumptions for defining and survey of variables, the protection of freedoms that reflect national values is identified in Brazilian legislation, and the sub-indices and the index are tested, applying them to understand the national, regional and State reality. The results showed that Brazil is in a “regular” condition of development, with an IDL of 0.50. It was evident the strong social vulnerability in the Northeast and North regions and the non-fulfillment of social needs by governmental spheres at the demanded level, an affirmation reinforced by the low and the regular sub-index they obtained for Social Opportunities. There is a concentration of wealth in the South, Southeast and Midwest of the country and more access to the opportunities, and in the Northeast there are a greater number of States with low socioeconomic performance.